Arginine methylation regulates the p53 response - Jansson, Martin; Durant, Stephen T.; Cho, Er-Chieh; Sheahan, Sharon; Edelmann, Mariola; Kessler, Benedikt; La Thangue, Nicholas B. (Nature cell biology, 2008)
The tumour suppressor p53 is subject to complex regulation and arginine methylation is now shown to provide an additional level of control. The protein arginine methyltransferase (PRMT) 5 is recruited by Strap to methylate p53 in response to DNA damage, governing the p53 response. Activation of the p53 tumour suppressor protein in response to DNA damage leads to apoptosis or cell-cycle arrest. Enzymatic modifications are widely believed to affect and regulate p53 activity. We describe here a level of post-translational control that has an important functional consequence on the p53 response. We show that the protein arginine methyltransferase (PRMT) 5, as a co-factor in a DNA damage responsive co-activator complex that interacts with p53, is responsible for methylating p53. Arginine methylation is regulated during the p53 response and affects the target gene specificity of p53. Furthermore, PRMT5 depletion triggers p53-dependent apoptosis. Thus, methylation on arginine residues is an underlying mechanism of control during the p53 response.